2013
DOI: 10.1002/acr.21929
|View full text |Cite
|
Sign up to set email alerts
|

Contemporaneous Severity of Symptoms and Functioning Reflected by Variations in Reporting Doctor‐Diagnosed Osteoarthritis

Abstract: Objective. Osteoarthritis (OA) is acknowledged as an enduring condition; however, in epidemiologic studies, half of the participants who report having OA at one time may report not having it at a subsequent time. The aim of this study was to examine whether variations in reporting doctor-diagnosed OA reflected concurrent fluctuations in indicators of disease severity in middle-aged women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Cancer information included in the study has been validated against Cancer Registry data with 89% sensitivity and 97% specificity [ 32 ]. Several other studies have demonstrated the validity of self-reported conditions, BMI, physical activity, and other risk factors [ 19 , 33 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer information included in the study has been validated against Cancer Registry data with 89% sensitivity and 97% specificity [ 32 ]. Several other studies have demonstrated the validity of self-reported conditions, BMI, physical activity, and other risk factors [ 19 , 33 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…We chose to examine joint symptoms rather than using a formal OA diagnosis, as many women in this age range may not have been diagnosed formally, using, for example, medical imaging. Previous research in this sample showed that fluctuations in joint symptoms coincided with within‐person variation in the self‐report of OA . Two definitions of joint symptoms were used: prevalent joint symptoms (reflecting the presence of symptoms at the end of the followup, irrespective of symptoms perceived during followup), and cumulative incident joint symptoms (reflecting the presence of joint symptoms during followup after the exclusion of those reporting symptoms at the start of the followup).…”
Section: Discussionmentioning
confidence: 99%
“…In each survey, participants were asked to indicate the frequency of experiencing joint pain and stiffness in the last 12 months, with the response options being never, rarely, sometimes, and often. Having joint symptoms was defined as having joint pain and stiffness often at each survey . Two outcome variables were created.…”
Section: Methodsmentioning
confidence: 99%
“…Our definition of first report of OA is as valid and as robust as possible from a community‐based survey. Defining arthritis by self‐report is always problematic; however, our previous research has shown that women were much more likely to report joint symptoms (pain and stiffness) when they reported having OA than when they did not report having OA (odds ratio for within‐person association: 7.3 [95%CI:7.1–7.5]), 25 and we can argue that self‐report OA is a measure of symptomatic OA. Furthermore, a recent systematic review of diagnostic accuracy showed that self‐report has acceptable validity when used in population‐based studies where rheumatologist examination is not feasible 26 .…”
Section: Discussionmentioning
confidence: 95%